A comparison of element agglomeration algorithms for unstructured geometric multigrid - Dargaville,S; Buchan,AG; Smedley-Stevenson,RP; Smith,PN; Pain,CC (arXiv, 2020)
This paper compares the performance of seven different element agglomerationalgorithms on unstructured triangular/tetrahedral meshes when used as part of ageometric multigrid. Five of these algorithms come from the literature on AMGemultigrid and mesh partitioning methods. The resulting multigrid schemes aretested matrix-free on two problems in 2D and 3D taken from radiation transportapplications; one of which is in the diffusion limit. In two dimensions allcoarsening algorithms result in multigrid methods which perform similarly, butin three dimensions aggressive element agglomeration performed by METISproduces the shortest runtimes and multigrid setup times.